(untitled) (Revista Lusófona de Educação, 2024)
Context and Objective: In the context of teacher training, in the Masters in Teaching Didactics, in particular in the curricular unit of Initiation to Professional Practice, the Masters students, Supervised Teaching Practice Students, carry out this practice in the field, with the Cooperating Guidance Teachers. Special importance is given to the evidence gathered in the classroom, which is why training centered on practice, a culture of research, collaboration and the quality of teaching supervision are highlighted. As it is a collaborative practice, it implies mutual growth and for this reason we raised the following question: “What is the contribution of the dynamics of supervised teaching practices to the transformation of teaching practices at school?” Based on this question, we have the following objectives: 1) To analyze the possible contributions of the trainees’ practices in the (trans)formation of the teaching practices of the experienced teachers at the school. 2) To analyze the impact of the performance of the cooperating supervisor’s duties on their professional development. 3) To understand the contribution of the research component during initial teacher training. Method: An interpretative and phenomenological qualitative study was carried out, with the interviewees being interviewed in the school environment. Data was collected by interviewing ten trainee teachers at the end of their internship and nine Cooperating Guidance Teachers from five schools. Results: The most frequent expressions of the Cooperating Guidance Teachers and the trainee teachers in relation to supervisory models and styles are “dialog”, “reflection” and “collaboration”. Collaboration is also an expression that both cooperating supervising teachers and trainees focus on. Conclusion: The high frequency of the expression “collaboration” highlights the relevance of this assumption throughout the supervisory process. When cooperating supervisors work collaboratively with their trainees, they benefit from this dyadic relationship, both in terms of the trainee’s professional practice and the performance of their duties as a teacher, and this benefit is reflected throughout the community, contributing to the professional growth of the Cooperating Supervising Teacher. Keywords: pedagogy; supervised teaching practices; cooperating guidance teacher; training.